Controle de demanda e formação de microrredes com grupos moto-geradores distribuídos - Domeneghi, Guilherme Monego (2019)
The present work developed a methodology that was applied in a study that had as a starting point the peak shaving of an electrical installation, aiming at the reduction of costs with the energy bill. To achieve this, the emergency and stand-by power generation systems were used, that has as main source the Diesel Generating Sets (gensets). The main focus was on the technical aspects that surround the parallelism of these machines with the electric power distribution network and also on the formation of microgrids in three moments of operation, parallel to the distribution network, isolated operation and parallelism between microgrids. After the development of the methodology, a real network of energy distribution was chosen for its application. The distribution system was modeled, as well as its gensets, into appropriate programs for simulations of power flow and dynamic stability. The simulations were carried out in a variety of cases, always taking into account the maximum demand already registered in the system, based on the highest load billed by the local utility. From the system model and the geographic arrangement of the generators, and by the considerable size of the network, there was a division in the feeders, so that the creation of microgrids was favored. Thus, the network was divided into six regions, and in three of them the load was very close to generation capacity, thus forming three distinct microgrids. All simulations focused on studying the transients that affect the frequency, magnitude and angle of the voltage, at the moments in-between the connection and disconnection of the microgrids with the distribution system. Some other aspects were also analyzed, such as the voltage levels presented in the network without and with the parallelism of the gensets and the electrical losses of the system in the same cases. The voltages of the base case were compared with those of the other cases. A specific case of overload of the microgrids has also been studied, aiming to observe what happens in this situation and the transients that the parallelism of them with the distribution system, without respecting the IEEE recommendations, can cause.